Combination of Lemon Aromatherapy and PC 6 Acupressure in Pregnancy Nausea Vomiting Trimester I - Meika Jaya Rochkmana; Widiyowati Widiyowati; Dwi Kustriyanti (Jurnal MID-Z (MIDWIFERI ZIGOT), 2023)
Morning sickness occurs in early pregnancy which is characterized by nausea and vomiting. Management can use a combination of lemon aromatherapy and acupressure pericardium 6 (PC 6). Purpose of the study: To determine the effect of the combination of lemon aromatherapy and PC6 acupressure on nausea and vomiting in first trimester pregnant women. Methods: This type of research was quasi-experimental with one group pr test post test design. The research sample was 17 respondents with purposive sampling technique. The research instrument was the PUQE 24 questionnaire. The research was carried out by giving the PUQE 24 questionnaire before and after the intervention. The combination intervention of lemon aromatherapy and PC 6 acupressure was given once a day for 4 consecutive days according to the SOP. Result: There is an effect of combination of lemon aromatherapy and PC 6 acupressure on nausea and vomiting in first trimester pregnant women with value of 0.000. Conclusion: the combination of lemon aromatherapy and PC 6 acupressure can be used as an alternative to treat nausea and vomiting in first trimester pregnant women.